Electrical-optical properties of nanofiber ZnO film grown by sol gel method and fabrication of ZnO/p-Si heterojunction - Mansour, Sh. A.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2012)
Electrical and optical properties of the ZnO film prepared by sol-gel dip coating were investigated and ZnO film was deposited onto p-type silicon to obtain Ag/ZnO/p-Si heterojunction diode. Two dimensional atomic force microscopy images indicate that the ZnO film is formed from the fibers consisted from nanoparticles with grain size of 250-350 nm. The electrical conductivity mechanism of the ZnO film was varied from extrinsic to intrinsic conductivity. The calculated optical band gap of the ZnO film was found to be 3.22 eV. The Ag/ZnO/p-Si diode exhibit a non-linear behavior with ideality factor of n = 417 and barrier height of phi(B) = 0.79 eV. The electrical properties of the Ag/ZnO/p-Si diode were investigated by current voltage, capacitance-voltage-frequency and conductance-voltage-frequency measurements. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: Nanofiber ZnO; Schottky diode; Semiconductor